2010
DOI: 10.1111/j.1365-3156.2010.02510.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported barriers and drivers of adherence to antiretrovirals in sub‐Saharan Africa: a meta‐ethnography

Abstract: This meta-ethnography aims at providing a synthesis and an interpretation of the findings of recent social science research on the questions of retention in antiretroviral therapy (ART) programmes in sub-Saharan Africa (SSA). The literature reviewed comprises ethnographic studies of the barriers to adherence to ART in various cultural settings. The results show that the quality of services, treatment-related costs, as well as the need to maintain social support networks - which can be negatively affected by HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
143
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(159 citation statements)
references
References 59 publications
(65 reference statements)
9
143
1
1
Order By: Relevance
“…A systematic review identified fear of disclosure, forgetfulness, lack of understanding of treatment benefits and leaving behind medications, to be common barriers to ART adherence in developed and developing countries, while problems of access, including financial constraints and disruption in drug supplies were specific to developing countries 14 . Failure to disclose HIV serostatus, poor social and family support, concurrent use of other medications with ART have also been found to be associated with poor ART adherence [14][15][16][17][18] . Adolescents have been found to be less adherent to ART than adults and younger children, while orphanhood and lack of social support have also been reported to be associated with poor ART adherence 15,[19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review identified fear of disclosure, forgetfulness, lack of understanding of treatment benefits and leaving behind medications, to be common barriers to ART adherence in developed and developing countries, while problems of access, including financial constraints and disruption in drug supplies were specific to developing countries 14 . Failure to disclose HIV serostatus, poor social and family support, concurrent use of other medications with ART have also been found to be associated with poor ART adherence [14][15][16][17][18] . Adolescents have been found to be less adherent to ART than adults and younger children, while orphanhood and lack of social support have also been reported to be associated with poor ART adherence 15,[19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Failure to disclose HIV serostatus, poor social and family support, concurrent use of other medications with ART have also been found to be associated with poor ART adherence [14][15][16][17][18] . Adolescents have been found to be less adherent to ART than adults and younger children, while orphanhood and lack of social support have also been reported to be associated with poor ART adherence 15,[19][20][21] . Standardised approaches are often used to enhance improvement in adherence to ART, however this may not be appropriate in all cases as this paper illustrates.…”
Section: Introductionmentioning
confidence: 99%
“…Discourses of the care cascade imply certain kinds of patient expectation and responsibility. An extensive body of extant literature accentuates how social and environmental factors shape HIV treatment provision and engagement (Gari et al, 2013;Merten et al, 2010;Underwood, Hendrickson, Van Lith, Kunda, and Mallalieu, 2014). Additionally, critical perspectives in the social sciences have reflected upon HIV and its care as constituted through situated health practices, identities and subjectivities, with implications for different social and political contexts Whyte, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A eficácia do tratamento está relacionada à sua adesão, no entanto, sua manutenção durante todo o tratamento é um problema [3][4][5]. A qualidade dos serviços de saúde, os custos relacionados com o TARV e a manutenção das redes de apoio social podem ser afetadas pelo estigma relacionado ao HIV, constituindo-se fatores que influenciam a adesão e tornando necessária a manutenção do equilíbrio entre a saúde física com a integridade social [6].…”
Section: Introductionunclassified